Dispersal Movements and Hot Spot Areas of Juvenile Bonelli's Eagles on the Island of Crete, Greece - Stavros Xirouchakis; Konstantinos Damianakis; Afroditi Kardamaki; Aspasia Anagnostopoulou (Пернатые хищники и их охрана)
The Bonelli’s Eagle (Aquila fasciata) is the main avian predator in almost all the islands of the Greek archipelagos. The phase of its natal dispersal has never been studied in Greece, though it constitutes a crucial part of the species ecology and conservation. In an effort to investigate the movement patterns and settlement areas of young eagles, we tagged 30 fledglings on the island of Crete during 2019–2023 with GPS/GSM transmitters.